Company Stock Price: Economic Value Added (EVA) and Market Value Added (MVA) - Mohamad Rafki Nazar; Abyan Talendyo Dwiarso (Jurnal E-Bis, 2023)
The existence of a banking company in Indonesia very important because it regulates financial transaction activities in Indonesia so that the company's share price continues to fluctuate. This study intends to identify the drivers of changes in banking stock prices between 2018 and 2021 based on added economic value and market added value. This research is quantitative and uses techniques purposive sampling in determining the sample criteria. There are 20 firms that satisfy the requirements, yielding 80 observational data. Using E-views 12 software and panel data regression analysis. The findings indicate that market added value and variable added economic value have an impact on stock prices at the same time. However, the only variable market added value that has an impact on stock prices. Other variables, such as financial added value, asset return, and others, might be used in future study.